An integrative framework for formal and informal entrepreneurship research in Africa - Richard Adu-Gyamfi; John E. Kuada; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
It is a well-established practice of many Sub-Sahara African (SSA) governments to aid entrepreneurs within both the formal and informal sectors in order to enhance their performance and growth. Unfortunately, there is no agreed method by which governments can differentiate between entrepreneurs and target them with the appropriate promotion policies. Thus, despite the good intentions, entrepreneurship policy initiatives have been incorrectly targeted, poorly implemented and without the desired results, since different entrepreneurs may require different forms of assistance. Some scholars have suggested that without a context-specific classificatory guide, policymakers are unlikely to be accurate in their assessment of the growth capabilities of prospective candidates for specific promotion initiatives and this can explain some of the policy failures. This observation has motivated the present paper. Our objective is to provide a framework that helps identify the different contextual dimensions influencing formal and informal enterprise creation processes in SSA.
Keywords: 330; entrepreneurship; formal; informal; Africa